Uva-ursi extract and ibuprofen as alternative treatments for uncomplicated urinary tract infection in women (ATAFUTI): a factorial randomized trial. (August 2019) - Moore, M.; Trill, J.; Simpson, C.; Webley, F.; Radford, M.; Stanton, L.; Maishman, T.; Galanopoulou, A.; Flower, A.; Eyles, C.; Willcox, M.; Hay, A.D.; et al.
Abstract: Objectives: The aim was to investigate if offering symptomatic therapy (Uva-ursi or ibuprofen) alongside a delayed prescription would relieve symptoms and reduce the consumption of antibiotics for adult women presenting with acute uncomplicated urinary tract infection (UTI). Methods: A 2 × 2 factorial placebo controlled randomized trial in primary care. The participants were 382 women aged 18–70 years with symptoms of dysuria, urgency, or frequency of urination and suspected by a clinician to have a lower UTI. The interventions were Uva-ursi extract and/or ibuprofen advice. All women were provided with a delayed or 'back-up' prescription for antibiotics. Missing data were imputed using multiple imputation methods (ISRCTN registry: ISRCTN43397016). Results: An ITT analysis of mean score for frequency symptoms assessed on Days 2–4 found no evidence of a difference between Uva-ursi vs. placebo –0.06 (95% CI –0.33 to 0.21; p 0.661), nor ibuprofen vs. no ibuprofen advice –0.01 (95% CI –0.27 to 0.26; p 0.951). There was no evidence of a reduction in antibiotic consumption with Uva-ursi (39.9% vs. placebo 47.4%; logistic regression odds ratio (OR) 0.59 (95% CI 0.22–1.58; p 0.293) but there was a significant reduction for ibuprofen advice (34.9% vs. no advice 51.0%; OR 0.27 (95% CI 0.10 to 0.72; p 0.009). There were no safety concerns and no episodes of upper tract infection were recorded. Conclusions: We found no evidence of an effect of either intervention on the severity of frequency symptoms. There is evidence that advice to take ibuprofen will reduce antibiotic consumption without increasing complications. For every seven women given this advice, one less will use antibiotics.